Prophylaxis for families with an alcohol problem - Łukowski, Karol (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
Prevention for families with alcohol problems shows the range of possibilities that families can use. Prevention creates conditions for change, it gives benefits and provides knowledge. In the paper I will present an extended range of options for universal, indicative and selective prevention. The alcohol prevention described concerns education, support methods, therapeutic interactions and obtaining necessary information. The main purpose of preventive measures is to reduce the negative effects of alcohol drinking in families. The article consists of an introductory part, a description of alcohol prevention for families, family psychoeducation, activities supporting alcohol prevention and a summary.